Kohelet und der materielle Reichtum. Koh 5,12–6,12 als eine Konkretisierung seines weisheitlichen Denkens - Moosbrugger, Mathias (Protokolle zur Bibel, 2007)
The book of Ecclesiastes as one of the few parts of the bible, which is in the very spotlight of modern forms of spirituality, is very likely to be misunderstood as a book promoting hedonism and irresponsibility - not only by common people, but also by theologians and exegetes. In contrary this essay tries to read Ecclesiastes regarding the cultural background of the accelerating hellenization of the Israelite world, which nevertheless appears to be quite a stable foundation. Thus, there is no understanding of difficult passages such as Ecclesiastes 5:12-6:12, which is one of the most important parts of this book as far as hermeneutics is concerned, if the traditional Israelite point of view is neglected. A closer look on these verses, which deal with the problematic phenomenon of material fortune, exemplifies that the author of Ecclesiastes is neither a cynic hedonist nor an indifferentstoic, but a wise man standing with both feet on the ground of traditional-biblical convictions. He uses the popular hellenistic philosophy as a tool not in order to create a new philosophy-based Weltanschauung, but to find new forms of legitimation of the old Israelite faith in times of a changing cultural world.